VIAŢA CAPITALEI PRIN PRISMA UNEI BIBLIOGRAFII - BULDUMA, şef serviciu, Departamentul „Memoria Chişinăului”, Gabriela (BIBLIOPOLIS, 2020)
The article presents the Bibliography of Chișinău, product of the Department "Chișinău memory" of the Municipal Library "B.P. Hasdeu". This paper provides a review of social, political, cultural, economic life of the city, reflecting facts, circumstances of past events, positive and negative changes in the activity of institutions and personalities who have contributed to promote the image of the city. Bibliography of Chişinău is like a "notch" containing notes about all the chapters of Chișinău history.